Strategic Management in Realizing Early Prevention and Management Programs for Solok Natural Disaster Victims - Detira, Zahara; Juwono, Vishnu (Interdisciplinary Social Studies, 2023)
Background: The Solok district regional disaster management agency (BPBD) has an obligation in handling natural disasters which is directly responsible to the community by holding activities in the form of education and outreach to natural disasters in the form of training programs held directly by the Solok district BPBD, in carrying out this activity the Solok district BPBD conducts strategic management to assist in running the program so that the program can run well according to the target by making the vision and mission a benchmark in program implementation. Aim: This study aims to determine the strategies and strategic management processes carried out by BPBD Solok district so that early prevention programs and relief for victims of natural disasters can be realized. Methods: This study used a qualitative approach with in-depth interview research methods to BPBD Solok district employees and direct observation at the BPBD Solok district. Findings: The results of this study explain the positive impact given in program implementation by conducting strategic management of activities by conducting a SWOT analysis. With strategic management, it is necessary to socialize the Solok district BPBD to the public regarding the Solok district BPBD programs.